Acute Pancreatitis Complicating Acute Hepatitis E Virus Infection: A Case Report and Review. (31st January 2013) - Nayak, Hemanta Kumar; Kamble, Nitish L.; Raizada, Nishant; Garg, Sandeep; Daga, Mradul Kumar
Abstract : Acute pancreatitis complicating fulminant viral hepatitis has been well recognized; however, acute pancreatitis occurring in nonfulminant hepatitis is very rare. The case presented describes moderate pancreatitis in a young male, manifesting during the course of nonfulminant acute hepatitis E infection. The diagnosis of acute viral hepatitis E was confirmed by serology and reverse transcriptase polymerase chain reaction (RT-PCR) to demonstrate Hepatitis E virus (HEV) RNA in both stool and serum. Patients with acute viral hepatitis presenting with severe abdominal pain should have a diagnosis of acute pancreatitis suspected and appropriate investigations including serum amylase, lipase, biliary ultrasonography and/or contrast-enhanced computed tomography of the abdomen should be undertaken. The identification of this unusual complication of Hepatitis E is important; however, the prognosis for patients with Acute Pancreatitis Complicating Acute Hepatitis E Virus Infection is good, and uncomplicated recovery with conservative treatment is expected.